Apoptosis of Acanthamoeba castellanii Trophozoites Induced by Oleic Acid. (28th August 2017) - Wu, Duo; Qiao, Ke; Feng, Meng; Fu, Yongfeng; Cai, Junlong; Deng, Yihong; Tachibana, Hiroshi; Cheng, Xunjia
Abstract: Acanthamoeba spp. can be parasitic in certain situations and are responsible for serious human infections, including Acanthamoeba keratitis, granulomatous amoebic encephalitis, and cutaneous acanthamoebiasis. We analyzed the fatty acid composition of Acanthamoeba castellanii trophozoites and tested the inhibitory activity of the main fatty acids, oleic acid and arachidonic acid, in vitro. Oleic acid markedly inhibited the growth of A. castellanii, with trophozoite viability of 57.4% at a concentration of 200 μM. Caspase‐3 staining and annexin V assays showed that apoptotic death occurred in A. castellanii trophozoites. Quantitative PCR and dot blot analysis showed increased levels of metacaspase and interleukin‐1β converting enzyme, which is also an indication of apoptosis. In contrast, arachidonic acid showed negligible inhibition of growth of A. castellanii trophozoites. Stimulated expression of Atg3, Atg8 and LC3A/B genes and monodansylcadaverine labeling suggested that oleic acid induces apoptosis by triggering autophagy of trophozoites.